Longitudinal Associations of Religiosity and Physical Function in Older Irish Adults. - Mc Garrigle, Christine; Kenny, Rose (My University, 2020)
Objectives: Research into the link between religion and physical function has shown inconsistent results. Most studies have used self-reported measures of physical function, and many have excluded those who are not religious and only compared levels of religious engagement within those groups that are religious. We aimed to assess the longitudinal associations of religious affiliation and religious attendance on two objective measures of physical function. Design: Longitudinal study using five waves of data from the Irish Longitudinal Study on Ageing (TILDA). Setting: Community-dwelling adults in Ireland. Participants: Adults aged 50 and over who participated in two or more waves of TILDA (n = 6,122),and a supplementary analysis of a sub-sample aged 65 and over (n = 2,359). Measurements: Timed Up and Go (TUG) and grip strength were measured on at least two occasions. Data were collected approximately every 2 years over 10 years. Longitudinal linear mixed effects models were estimated to calculate the effect of religious affiliation and attendance on TUG and grip strength over time. Results: TUG scores increased by an average of .1 seconds with each year of age, which increased to .3 seconds by age 72 years. Grip strength scores decreased by .2 kg with each year of age and increased to -.3 kg per year by age 72. No overall differences were observed between religious affiliations in scores of TUG or grip strength. Conclusion: Religious affiliation does not predict performance on objective physical function measures. Results are discussed with reference to the changing religious characteristics of the Irish population.
PUBLISHED
Keywords: Timed Up and Go, grip strength, longitudinal, religion; Ageing